PEMBERLAKUAN PERJANJIAN INVESTASI BILATERAL (BILATERAL INVESTMENT TREATIES) DI SEKTOR KELAUTAN DAN PERIKANAN DI INDONESIA - Salsabila Salsabila (UNES Law Review, 2023)
The Bilateral Investment Agreement is one of the ways that the Indonesian government and other countries have implemented to support the implementation of foreign investment in Indonesia in the hope that mutually beneficial conditions will be created for the two countries, especially with the existence of principles regarding standard of treatment in a BIT. which is expected to provide protection for both parties. This research was conducted using a normative juridical approach by conducting research on legal principles and using analytical descriptive methods. Indirect expropriation is something that can be done by the Indonesian government in supervising foreign companies operating in Indonesia, thus it is hoped that it will reduce losses experienced by Indonesia in carrying out foreign investment so that people's welfare will be realized.